Optimal placement and sizing of distributed generation unit by loading margin approach for voltage stability enhancement - Nasirah Mamat, 1985- , author; Mohd. Wazir Mustafa, supervisor; Fakulti Kejuruteraan Elektrik (2015)
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2015